The Impact of Matching Activities on Fine Motor Skill Development in Young Children - Dede Nurul Qomariah; Rini Novianti Yusuf; Yesa Pratami; Tri Aismi Paulihah; Meli Roswiyanti (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This study aims to explore how to improve children’s fine motor skills through matching activities. This study employed a classroom action research method conducted in two cycles, consisting of the following stages: planning, implementation, observation, and reflection. The research subjects consisted of 15 children, namely 6 girls and 9 boys. The results showed an improvement in the children’s fine motor skills from Cycle I to Cycle II. In Cycle I, the percentages were BB 7.14%, MB 35.71%, BSH 21.42%, and BSB 35.71%. In Cycle II, these percentages increased to 0.0% for BB, 26.66% for MB, 26.66% for BSH, and 46.66% for BSB. Thus, it can be concluded that the picture-matching activity proved effective in improving children’s fine motor skills.